Development of normal reference intervals for renal function in pregnancy: a secondary analysis of clinical trial data - Zandile Legoabe; Motshedisi Sebitloane; Carl Lombard; Megeshinee Naidoo; Glenda Gray; Dhayendre Moodley (Journal of Obstetrics and Gynaecology)
Background Due to its potential nephrotoxicity, screening for pre-existing renal function disorders has become a routine clinical assessment for initiating Tenofovir diphosphate fumarate (TDF)-containing antiretroviral treatment (ART) or pre-exposure prophylaxis (PrEP) in pregnant and non-pregnant adults. We aimed to establish reference values for commonly used markers of renal function in healthy pregnant women of African origin.Methods Pregnant women ≥18 years, not living with HIV, and at 14–28 weeks gestation were enrolled in a PrEP clinical trial in Durban, South Africa between September 2017 and December 2019. Women were monitored 4-weekly during pregnancy until six months postpartum. We measured maternal weight and serum creatinine (sCr) at each visit and calculated creatinine clearance (CrCl) rates using the Cockcroft–Gault (CG) and Modification of Diet in Renal Disease (MDRD) formulae. Reference ranges for sCr and CrCl by CG and MDRD calculations were derived from the mean ± 2SD of values for pregnancy and postdelivery.Results Between 14-–and 40 weeks gestation, 249 African women not exposed to TDF-PrEP contributed a total of 1193 renal function values. Postdelivery, 207 of these women contributed to 800 renal function values. The normal reference range for sCr was 30–57 and 32–60 umol/l in the 2nd and 3rd trimesters of pregnancy. Normal reference ranges for CrCl using the MDRD calculation were 129–282 and 119–267 ml/min/1.73m2 for the 2nd and 3rd trimesters, respectively. Using the CG method of calculation, normal reference ranges for CrCl were 120—304 and 123–309 ml/min/1.73m2 for the 2nd and 3rd trimesters respectively. In comparison, the normal reference range for sCr, CrCl by MDRD and CG calculations postpartum was 40–77 umol/l, 92–201, and 90–238 ml/min/1.73m2, respectively.Conclusions In African women, the Upper Limit of Normal (ULN) for sCr in pregnancy is approximately 20% lower than 6 months postnatally. Inversely, the Lower Limit of Normal (LLN) for CrCl using either MDRD or CG equation is approximately 35% higher than 6 months postnatally. We provide normal reference ranges for sCr and CrCl for both methods of calculation and appropriate for the 2nd and 3rd trimesters of pregnancy in African women.